Inequalities of Eigenvalues for Uniformly Elliptic Operators with Higher Orders (Journal of Partial Differential Equations, 2020)
Let (Ω) ⊂ R^m (m ≥ 2) be a bounded domain with piecewise smooth boundary ∂Ω. Let t be positive integer with t > 1. We consider the eigenvalue problems about (1.1) and (1.2), and obtain Theorem 2.1 and Theorem 2.2, which are generalizations of the results in [1-2]. This kind of problem is interesting and significant both in theory of partial differential equations and in applications to mechanics and physics.
Keywords: Uniformly elliptic operators with higher orders; eigenvalues; eigenfuctions